"Choice may not necessarily be a good thing": student attitudes to autonomy in interdisciplinary project-based learning in GEES disciplines. Issue 4 (1st October 2016) - Harmer, Nichola; Stokes, Alison
Abstract: Project-based learning (PjBL) is argued to foster a more democratic approach to education, particularly through increasing students' autonomy over their learning. This article presents the findings of research into students' views relating to autonomy over topic choice and group constitution during a series of trial interdisciplinary PjBL activities with first-year geography, earth and environmental sciences (GEES) undergraduates in a UK university. Semi-structured interviews with participating students and tutors, in addition to audio-recordings of staff–student discussion during student-led presentation sessions, formed the data set analysed for this article. Findings suggest that while some degree of autonomy was welcomed, participants largely favoured prescription regarding research question and group membership. This has implications for the implementation of PjBL and its potential to foster democratization within the GEES disciplines.